Occurrence and molecular characteristics of antimicrobial resistance of Escherichia coli from broilers, pigs and meat products in Thailand and Cambodia provinces. (23rd September 2016) - Trongjit, Suthathip; Angkittitrakul, Sunpetch; Chuanchuen, Rungtip
ABSTRACT: Nine hundred and forty‐one samples were collected in Sa Keao, Thailand ( n = 554) and Banteay Meanchey, Cambodia ( n = 387) from July 2014 to January 2015. A total of 667 Escherichia coli isolates (381 isolates from Sa Keao and 286 isolates from Banteay Meanchey) were obtained and examined for antimicrobial susceptibility, class 1 integrons, ESBL genes and horizontal transfer of resistance determinants. Prevalence of E. coli in pig and broiler carcass samples from slaughterhouses and fresh markets was 36–85% in Sa Keao and 11–69% in Banteay Meanchey. The majority of these isolates were multidrug resistant (75.3%). Class 1 integrons were common in both Thai (47%) and Cambodian (62%) isolates, of which four resistance gene cassette arrays including aadA1, dfrA1‐aadA1, dfrA12‐aadA2 and aadA2‐linF were identified. Class 1 integrons in two broiler isolates from Sa Keao ( dfrA12‐aadA2 ) and one broiler isolate from Banteay Meanchey ( dfrA1‐aadA1 ) were horizontally transferable. Sixteen isolates were confirmed to be ESBL‐producing strains with ESBL gene bla CTX‐M‐15, broad spectrum β‐lactamase gene bla TEM‐1 and the AmpC gene bla CMY‐2 being detected. The bla TEM‐1 gene was most prevalent and located on a conjugative plasmid.